Causes of Child and Youth Homelessness in Developed and Developing Countries: A Systematic Review and Meta-analysis - Embleton, Lonnie (JAMA Pediatr, 2016)
IMPORTANCE: A systematic compilation of children and youth’s reported reasons for street involvement is lacking. Without empirical data on these reasons, the policies developed or implemented to mitigate street involvement are not responsive to the needs of these children and youth. OBJECTIVE: To systematically analyze the self-reported reasons why children and youth around the world become street-involved and to analyze the available data by level of human development, geographic region, and sex. DATA SOURCES: Electronic searches of Scopus, PsychINFO, EMBASE, POPLINE, PubMed, ERIC, and the Social Sciences Citation Index were conducted from January 1, 1990, to the third week of July 2013. We searched the peer-reviewed literature for studies that reported quantitative reasons for street involvement. The following broad search strategy was used to search the databases: “street children” OR “street youth” OR “homeless youth” OR “homeless children” OR “runaway children” OR “runaway youth” or “homeless persons.” STUDY SELECTION: Studies were included if they met the following inclusion criteria: (1) participants were 24 years of age or younger, (2) participants met our definition of street-connected children and youth, and (3) the quantitative reasons for street involvement were reported. We reviewed 318 full texts and identified 49 eligible studies. DATA EXTRACTION AND SYNTHESIS: Data were extracted by 2 independent reviewers. We fit logistic mixed-effects models to estimate the pooled prevalence of each reason and to estimate subgroup pooled prevalence by development level or geographic region. The meta-analysis was conducted from February to August 2015. MAIN OUTCOMES AND MEASURES: We created the following categories based on the reported reasons in the literature: poverty, abuse, family conflict, delinquency, psychosocial health, and other. RESULTS: In total, there were 13 559 participants from 24 countries, of which 21 represented developing countries. The most commonly reported reason for street involvement was poverty, with a pooled-prevalence estimate of 39% (95% CI, 29%–51%). Forty-seven studies included in this review reported family conflict as the reason for street involvement, with a pooled prevalence of 32% (95% CI, 26%–39%). Abuse was equally reported in developing and developed countries as the reason for street involvement, with a pooled prevalence of 26% (95% CI, 18%–35%). Delinquency was the least frequently cited reason overall, with a pooled prevalence of 10% (95% CI, 5%–20%). CONCLUSIONS AND RELEVANCE: The street-connected children and youth who provided reasons for their street involvement infrequently identified delinquent behaviors for their circumstances and highlighted the role of poverty as a driving factor. They require support and protection, and governments globally are called on to reduce the socioeconomic inequities that cause children and youth to turn to the streets in the first place, in all regions of the world.